P80 Antiviral therapy in HCV cirrhotic patients: early on-treatment haematological parameters and genotype predict response. (16th November 2010) - Carey, I; Mendes, A; Joshi, D; Gera, A; Al-Freah, M; Knighton, S; Suddle, A; Agarwal, K
Abstract : Introduction: Pegylated interferon-a (Peg-IFN)+ribavirin (Riba) is standard of care for treatment of chronic hepatitis C (CH-C). Antiviral therapy is recommended in those with compensated disease and lower rates of treatment responses are noted with little data on predictors of outcome in this "difficult to treat" group. Aim: To assess pre-treatment, on treatment haematological, biochemical and clinical characteristics of patients with CH-C cirrhosis and response to antiviral therapy in a single centre cohort. Method: 66 patients with CH-C infection and cirrhosis (96% Child-Pugh A, median MELD 13 and UKELD 44), median age 51 years (range 21–70), 50 males; treated with Peg-IFN 2a and weight based Riba (13 mg/kg/day) according to their genotype (24–72 weeks) between July 2006 and December 2009. Patients were divided into 3 groups by response: sustained responders (SVR) n=20 (30%), relapsers (Rel) n=24 (37%) and non-responders (NR) n=22 (33%). Virological, biochemical and haematological parameters (HCV RNA viral load, HCV genotype (G), sodium, bilirubin, creatinine and albumin levels, prothrombin time, haemoglobin (Hb) levels and neutrophil (ANC), platelets (PLT) counts were assessed at baseline (W0) and at different timepoints: treatment week 4 (TW4), TW8, TW12, TW24 (G1&4) and at the end of therapy (EOT). Child-Pugh, MELD and UKELD scores were assessed and compared with outcome. Results: Baseline HCV RNA viral load was similar in SVR, Rel and NR. SVR was significantly lower (13% vs 54%, p<0.01) in G1&4 patients. No differences in Child-Pugh (median 5, range 5–12), MELD (median 13, range 10–16) and UKELD (median 44, range 39–50) scores at any point were detected. Baseline ANC and PLT (both ×10^9/ml) were lower in NR than SVR and Rel (median ANC: 2.43 vs 3.67 and 3.21, p=0.04 and median PLT: 122 vs 142 and 156, p=0.05). Baseline Hb levels (g/dl) were similar in all patients, but decreased significantly during therapy at TW4, TW8 and TW12 in SVR than in NR and Rel (TW4: 1.9 vs 1 vs 1.2, p=0.03; TW8: 2.6 vs 1.9 and 2.2, p=0.03 and TW12: 3.5 vs 2.8 vs3, p=0.04). There was no difference in dose reductions of Peg-IFN and Riba and use of haematological growth factors between groups. Conclusion: Antiviral therapy in our population was safe. Early decrease in Hb at W12 (perhaps reflecting inter-individual ribavirin concentration); HCV genotype, higher baseline ANC and PLT counts were associated with response.